A fuzzy decision model for the active and reactive dispatch in market environment - Mário Hélder Rodrigues Gomes (2006)
This paper presents a mathematical formulation for the active/reactive dispatch in electricity markets, recognizing that the typical sequential activities organized in terms of pool markets and the dispatch of ancillary services may lead to economic inefficiencies or technical difficulties. The developed model admits that it is known the purely economic pool dispatch and then it aims at dispatching reactive resources considering voltage and branch limit constraints and constraints reflecting the alternator capability curve. We also admitted that some constraints have a soft nature and used a symmetrical fuzzy decision formulation to model this aspect within an SLP based algorithm. Finally, the paper includes a case study based on the IEEE 24 bus/38 branch system to illustrate the results obtained with the developed approach.